“Aboriginal government through the negotiation of practical arrangements”: Indigenous–State Relations in 1990s New Brunswick - O’Byrne, Nicole; McGill, Karen (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2024)
Indigenous leaders have long argued that meaningful self-government requires revenue from natural resources to fund public policy initiatives that address the needs of their people. In the Marshall decisions, the Supreme Court recognized the ongoing commercial aspect of the treaty relationship between the Crown and First Nations. In this paper, we argue that the New Brunswick tax revenue sharing agreements were a manifestation of an evolving and modern treaty relationship in which resources and revenue can be shared for the benefit of all people living in the territory. The decision to cancel the agreements signals that the provincial government fails to understand that its role in a treaty relationship requires equitable sharing of resources—a principle confirmed and amplified by the Marshall decisions.